Impact of intercostal nerve blocks using liposomal versus standard bupivacaine on length of stay in minimally invasive thoracic surgery patients - Dominguez, Dana A.; Ely, Sora; Bach, Cynthia; Lee, Tina; Velotta, Jeffrey B. (Journal of Thoracic Disease, 2018)
Background: Postsurgical pain control can have a significant impact on patient outcomes and hospital-associated costs. We sought to evaluate the effect of intercostal nerve blocks using liposomal bupivacaine on length of stay (LOS) in patients undergoing video-assisted thoracoscopic surgery (VATS). Methods: We retrospectively reviewed outcomes in 80 patients undergoing VATS wedge resection, VATS lobectomy, or minimally-invasive esophagectomy (MIE). Patients received either liposomal bupivacaine (n=40) or standard-release bupivacaine with epinephrine (n=40) via intercostal nerve block. The LOS, 24-hour postoperative pain scores, overall opioid usage, and patient ambulation rates at 24 hours were compared for the two groups. Results: The median LOS was significantly shorter in patients receiving liposomal bupivacaine, at 1.35 days (IQR, 1.28 to 1.53 days) compared to 2.45 days (IQR, 2.08 to 3.51 days) in patients receiving standard-release bupivacaine (P